Numerical simulations of gas-liquid two-phase flow in Polymer Electrolyte Membrane fuel cells - Ding, Yulong (University of British Columbia, 2012)
Water management in PEM fuel cells has received extensive attention for its key role in fuel cell operation. Several water management issues have been identified that needed further investigation, i.e., droplet behaviour on the GDL surface, two-phase flow patterns in gas flow channels, impact of two-phase flow on PEM fuel cell performance, impact of flow mal-distribution on PEM fuel cell performance, and mitigation of flow maldistribution. In this work, those issues were investigated based on simulations using computational fluid dynamics (CFD) method. Using the Volume of Fluid (VOF) two-phase flow model, droplet behaviour and two-phase flow patterns in mini-channels were identified consistently in both simulations and experimental visualizations. The microstructure of the GDL was found to play a significant role in the formation of local two-phase flow patterns, and the wettability of both GDL and channel wall materials greatly impacted on the two-phase flow patterns. A novel 1+3D two-phase flow and reaction model was developed to study the impact of two-phase flow on PEM fuel cell performances. The existence of two-phase flow, especially the slug flow, in gas flow channels was found to be detrimental to the fuel cell performance and stability. Uneven liquid flow distribution into two parallel gas channels significantly reduces the fuel cell output voltage because of the induced severe non-uniform gas distribution, which should be avoided in the operation due to its negative effect on the fuel cell performance and durability. Finally, several maldistribution mitigation methods were tested in the simulation. It was found that utilizing narrow communication channels or adding gas inlet resistances could effectively reduce the gas flow maldistribution. === Applied Science, Faculty of === Chemical and Biological Engineering, Department of === Graduate